2013
DOI: 10.1186/1476-4598-12-169
|View full text |Cite
|
Sign up to set email alerts
|

CD98hc (SLC3A2) drives integrin-dependent renal cancer cell behavior

Abstract: BackgroundOverexpression of CD98hc (SLC3A2) occurs in a variety of cancers and is suspected to contribute to tumor growth. CD98, a heterodimeric transmembrane protein, physically associates with certain integrin β subunit cytoplasmic domains via its heavy chain, CD98hc. CD98hc regulates adhesion-induced intracellular signal transduction via integrins, thereby, affecting cell proliferation and clonal expansion. Disruption of CD98hc led to embryonic lethality in mice (E 3.5 and E 9.5) and CD98hc −/− embryonic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 27 publications
(50 reference statements)
3
53
0
Order By: Relevance
“…Particularly, crosslinking of CD98hc increased adhesion of the small cell lung-cancer cell line (SCLC) H345 and that of breast cancer cells to fibronectin and laminin by inducing conformational changes in β1 integrins [14,15]. The physical association of CD98hc with specific integrin β subunits is required for tumorigenesis of renal cancer cells via sustained FAK phosphorylation and activation of the PI3K/Akt and MEK/ERK signaling pathways [16]. Previous studies indicated that CD98hc-induced FAK phosphorylation was dependent on the β1 integrin-mediated signaling pathway [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, crosslinking of CD98hc increased adhesion of the small cell lung-cancer cell line (SCLC) H345 and that of breast cancer cells to fibronectin and laminin by inducing conformational changes in β1 integrins [14,15]. The physical association of CD98hc with specific integrin β subunits is required for tumorigenesis of renal cancer cells via sustained FAK phosphorylation and activation of the PI3K/Akt and MEK/ERK signaling pathways [16]. Previous studies indicated that CD98hc-induced FAK phosphorylation was dependent on the β1 integrin-mediated signaling pathway [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…While regulated activation of integrins is critical for tissue homeostasis, overexpressed β1-integrin detected in several types of human cancers indicated poor prognosis, and it is associated with metastasis and chemo-resistance of cancer cells [12,13,14]. Indeed, integrin-dependent events, such as survival, proliferation, migration and even malignant transformation can be activated by CD98 without integrin ligation or extracellular matrix engagement [10,15,16,17,18]. Recently, CD98 was reported to enable matrix assembly and support RhoA-driven contractility, and it contributed to carcinogenesis by amplifying a positive feedback loop, which increases both extracellular matrix stiffness and resulting cellular responses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Male mice of each genotype, [8][9][10] weeks old, were put on HFD for 16 weeks to allow the establishment of VSMC-rich atherosclerotic plaque.…”
Section: Cd98hc Loss Alters Atherosclerotic Plaque Morphology Towardsmentioning
confidence: 99%
“…The protein has dual functions, including transporting large, neutral amino acids via its interaction with various light chains, and mediating integrin signaling via its cytoplasmic tail, specifically β1-or β3-integrins 1314, 15 . Together, these functions serve to regulate cell survival, proliferation, migration and even malignant transformation 10,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation